Factors Influencing Supplementary Feeding Program Success among Stunted Children Under Five - Nur Fardian; Alma Lucyati; Ivan Adrian Montolalu (Mandalika Journal of Medical and Health Studies, 2026)
Background: Stunting remains a major public health challenge among children under five, particularly in low- and middle-income countries. Supplementary feeding programs have been widely implemented to improve nutritional status and reduce stunting; however, their effectiveness varies across contexts. Objective: This review aimed to identify and synthesize the factors influencing the success of supplementary feeding programs among stunted children under five. Methods: A Traditional Literature Review (TLR) was conducted using studies published between 2018 and 2026. Relevant literature was retrieved from Google Scholar, PubMed, Scopus-indexed sources, ScienceDirect, and publications from international organizations. The selected studies included systematic reviews, intervention studies, observational studies, qualitative investigations, implementation evaluations, and policy reports. Data were analyzed using thematic content analysis. Results: Four major determinants of program success were identified. Nutritional determinants included dietary diversity, micronutrient adequacy, feeding quality, and the nutritional composition of supplementary foods. Socioeconomic and environmental determinants comprised household food security, maternal education, sanitation, and healthcare access. Caregiver and family determinants involved nutrition knowledge, parental compliance, responsive feeding practices, and family support. Program implementation determinants included monitoring and evaluation systems, funding, community participation, resource availability, and implementation quality. Conclusion: The success of supplementary feeding programs among stunted children under five is influenced by interconnected nutritional, socioeconomic, caregiver-related, and implementation factors. Comprehensive and context-specific interventions are required to maximize program effectiveness and support sustainable stunting reduction.